Changes in DPPX autoantibody levels in autoimmune encephalitis: a case report and brief review - Abdalla Khabazeh; Volney Sheen (Brain Disorders)
Introduction: Dipeptidyl-peptidase-like protein-6 (DPPX) encephalitis is a recently recognized but rare cause of autoimmune encephalitis. Clinically, it presents with a subacute onset of seizures, cognitive decline, and tremors, often accompanied by gastrointestinal manifestations such as weight loss and vomiting. Temporal fluctuations in DPPX antibody levels have not been previously reported and diagnosing this subtype remains challenging due to its gradual onset, diverse clinical presentation, and possible fluctuations in antibody levels throughout the disease course. Its pathophysiology is incompletely understood, likely involving genetic, environmental, and immune factors. Case report: We describe a 22-year-old male presenting with a clinical syndrome consistent with DPPX encephalitis, including seizures, cognitive impairment, and systemic manifestations. Serum testing revealed antibodies to DPPX and voltage-gated potassium channels (VGKC), confirmed by a cell-based assay. The assay was repeated at the initial presentation and was again positive. However, repeat testing several months later, prior to treatment, showed negative cerebrospinal fluid (CSF) and serum DPPX antibodies. Repeat testing on a third occasion also returned negative results. The patient improved significantly after immunotherapy, consistent with an autoimmune encephalitis diagnosis. Conclusion: This case highlights the diagnostic challenges of DPPX encephalitis, emphasizing the importance of interpreting encephalopathy panel results within the clinical context. The observed fluctuations in DPPX antibody levels suggest that repeat serum testing may be of utility to reassess diagnosis and guide treatment in clinical cases where there is concern for autoimmune encephalitis.